Validitas dan Reliabilitas Instrumen Determinan Kepatuhan Minum Obat pada Pasien Lupus Eritematosus Sistemik: Validity and Reliability of Determinant Instrument of Medication Compliance on Systemic Lupus Erythematosus Patients - Sheba, Shiane Hanako (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2018)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease withunknown etiology so the patient needs long-term treatment to control theillness. It could impact physical and economic burden due to serious sideeffects and high cost treatment that affect drug adherence. The determinantsof drug adherence vary by location due to social, political and culturaldifferences. The aim of this study is to obtain a valid and reliable insrumentof drug adherence determinant for SLE patients. Quantitative research was conducted on 30 SLE patients at Rheumatologyclinic of Dr. Hasan Sadikin Hospital Bandung with consecutive samplingtechnique. Data was analyzed by Rasch model.The validity of 103 instrument item shows: 83 items are fit statistic; all itemsare unidimensional and no inter-items conflict; differences of 4 points scaleare understood by the respondent. Reliability shows: items reliability andstrata separation are excellent; responden reliability and strata separationare good; Cronbach's Alpha is excellent (0.88).The result of this study is a valid and reliable instrumen of drug adherencedeterminants for SLE patient, representing 51 constructs and 13 categories:individual characteristics, memory, knowledge, experimentation,consumption management, disease characteristics, drug characteristics,costs, hospital policies, access to hospitals, enabler agents, characteristicsof health proffesional and social support.